(untitled) (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
The province of North Sumatera, as one of advanced provinces in Sumatera Island, is expected to boost economies of other provinces. However, good economic level in North Sumatera Province has not been followed by equitable distribution of income between regions within. The value of Williamson Index shows the disparity that occurred in North Sumatera Province is still quite high. Nevertheless, someday relatively backward regions could catch up with relatively developed regions, so that inter-regional income levels may reach a relatively similar level, which is called economic convergence. This research aims to identify the tendency of economic convergence among regions in North Sumatera Province and to analyze the variables that influence the economic growth in order to realize economic convergence by using panel data regression approach. The result of the research shows the tendency of economic convergence in North Sumatera Province, while the variables that influence the economic convergence are capital expenditure, Human Development Index (HDI) and open unemployment rate.